Translation and Validation of the Greek Food Allergy Quality of Life Questionnaire—Parent Form - Emilia Vassilopoulou; Anna Comotti; Dafni Athanasaki; Gregorio Paolo Milani; Carlo Agostoni; George N. Konstantinou (Pediatric Reports)
Background: The prevalence of food allergy is increasing, posing a significant health concern. Assessing health-related quality of life (HRQOL) in individuals with food allergies is crucial, and various questionnaires exist for this purpose. However, translation and validation of these tools are necessary to ensure cultural relevance. This study aimed to translate the FAQLQ-PF into Greek and perform a cross-sectional validation to assess its effectiveness in evaluating HRQOL among Greek children with food allergies. Methods: Parents of children aged 0 to 12 years diagnosed with food allergy completed the Greek version of the FAQLQ-PF, consisting of 30 items across three subscales. Socio-demographic and clinical data were collected. Statistical analyses included nonparametric tests, correlation analysis for validity, and Cronbach’s alpha for internal consistency. Results: Out of 85 participants, 81 were included. The FAQLQ-PF demonstrated excellent internal consistency (Cronbach’s α = 0.94). Validity evaluation indicated its ability to measure HRQOL in younger children. HRQOL in the Greek pediatric population was significantly correlated with the number of food allergies, symptoms, parental and child concerns, anxiety levels, and activity restrictions. However, sex and general health status were not significantly correlated with HRQOL. Conclusions: The Greek translation and validation of FAQLQ-PF provides insights into HRQOL among Greek children with food allergies. Factors such as anaphylactic reactions, epinephrine autoinjector usage, number of food allergies, and symptoms influenced HRQOL in this population.